Dissolved Trace and Minor Elements in Cryoconite Holes and Supraglacial Streams, Canada Glacier, Antarctica - Fortner, Sarah K.; Lyons, W. Berry (Frontiers in Earth Science, 2018)
We present a synthesis of the trace element chemistry in melt on the surface Canada Glacier, Taylor Valley, McMurdo Dry Valleys (MDV), Antarctica (~78°S). The MDV is largely ice-free. Low accumulation rates, strong winds, and proximity to the valley floor make these glaciers dusty in comparison to their inland counterparts. This study examines both supraglacial melt streams and cryoconite holes. Supraglacial streams on the lower Canada Glacier have median dissolved (<0.4 μm) concentrations of Fe, Mn, As, Cu, and V of 71.5, 75.5, 3.7, 4.6, and 4.3 nM. All dissolved Cd concentrations and the vast majority of Pb values are below our analytical detection (i.e., 0.4 and 0.06 nM). Chemical behavior did not follow similar trends for eastern and western draining waters. Heterogeneity likely reflects distinctions eolian deposition, rock:water ratios, and hydrologic connectivity. Future increases in wind-delivered sediment will likely drive dynamic responses in melt chemistry. For elements above detection limits, dissolved concentrations in glacier surface melt are within an order of magnitude of concentrations observed in proglacial streams (i.e., flowing on the valley floor). The Fe enrichment of cryoconite water relative to N, P, or Si exceeds enrichment observed in marine phytoplankton. This suggests that the glacier surface is an important source of Fe to downstream ecosystems.